Clinical Efficacy and Safety of Surgical Treatments in Patients With Pure Cervical Radiculopathy - Gao, Quan-You; Wei, Fei-Long; Zhu, Kai-Long; Zhou, Cheng-Pei; Zhang, Hu; Cui, Wen-Xing; Li, Tian; Qian, Ji-Xian; Hao, Ding-Jun (Frontiers in Public Health, 2022)
Background: Traditionally paired meta-analysis revealed inconsistencies in the safety and effectiveness of surgical interventions. We conducted a network meta-analysis to assess various treatments' clinical efficacy and safety for pure cervical radiculopathy. Methods: The Embase, PubMed, and Cochrane Library databases were searched for randomized controlled trials (RCTs) comparing different treatment options for patients with pure cervical radiculopathy from inception until October 23, 2021. The primary outcomes were postoperative success rates, postoperative complication rates, and postoperative reoperation rates. The pooled data were subjected to a random-effects consistency model. The protocol was published in PROSPERO (CRD42021284819). Results: This study included 23 RCTs (n = 1844) that evaluated various treatments for patients with pure cervical radiculopathy. There were no statistical differences between treatments in the consistency model in terms of major clinical effectiveness and safety outcomes. Postoperative success rates were higher for anterior cervical foraminotomy (ACF: probability 38%), posterior cervical foraminotomy (PCF: 24%), and anterior cervical discectomy with fusion and additional plating (ACDFP: 21%). Postoperative complication rates ranked from high to low as follows: cervical disc replacement (CDR: probability 32%), physiotherapy (25%), ACF (25%). Autologous bone graft (ABG) had better relief from arm pain (probability 71%) and neck disability (71%). Among the seven surgical interventions with a statistical difference, anterior cervical discectomy with allograft bone graft plus plating (ABGP) had the shortest surgery time. Conclusions: According to current results, all surgical interventions can achieve satisfactory results, and there are no statistically significant differences. As a result, based on their strengths and patient-related factors, surgeons can exercise discretion in determining the appropriate surgical intervention for pure cervical radiculopathy.